Immune‐related dermatitis during combined treatment with pembrolizumab and axitinib in a patient with metastatic renal cell92carcinoma with stasis dermatitis. Issue 6 (5th August 2021) - Imai, Shunsuke; Nakamura, Masaki; Chujo, Satomi; Ooki, Ryousuke; Inoue, Yasushi; Horiuchi, Hajime; Morikawa, Teppei; Uchino, Keita; Igarashi, Atsuyuki; Shiga, Yoshiyuki
Abstract : Introduction: The combination of pembrolizumab and axitinib has recently been approved as a first‐line treatment for previously untreated metastatic renal cell carcinoma. However, immune‐related adverse events are not well known. Case presentation: A 65‐year‐old male was diagnosed with renal cell carcinoma with metastases to the brain and lungs. The patient had a medical history of stasis dermatitis. During the combined treatment of pembrolizumab and axitinib, blisters appeared on the lower extremities. Skin biopsy revealed septal panniculitis, pustules, and perivascular lymphocytic and neutrophilic infiltration of the skin, and the patient was diagnosed with immune‐related dermatitis. The dermatitis improved with oral prednisolone treatment. Conclusion: A case of immune‐related dermatitis during combinatorial treatment with pembrolizumab and axitinib for renal cell carcinoma has been reported. Preexisting stasis dermatitis may have affected the onset and deterioration of immune‐related dermatitis.